Sleep Apnea and Inflammation – Getting a Good Night’s Sleep with Omega-3 Supplementation - Scorza, Fulvio A.; Cavalheiro, Esper A.; Scorza, Carla A.; Galduróz, José C.; Tufik, Sergio; Andersen, Monica L. (Frontiers in Neurology, 2013)
Obstructive sleep apnea (OSA) is a multifactorial sleep disorder associated to increased risk for cardiovascular mortality and morbidity. Several mechanisms were proposed to explain the association between the occurrence of OSA and increased cardiovascular dysfunction. One of the proposed mechanisms is the inflammatory response to OSA mediated especially by tumor necrosis factor (TNF-α). Patients with OSA showed higher plasmatic, serum, and intracellular levels of TNF-α, which may be reduced after apnea treatment with continuous positive airway pressure (CPAP). Considering that TNF-α plays an important role in OSA related cardiovascular morbidity, the present review speculates if there is any preventive measure, besides the use of CPAP, which could minimize the inflammatory process in OSA and consequently the risk of premature death by cardiovascular dysfunctions. Thus, we hypothesized that a possible answer for this question is the nutritional immunology profile, or rather, more precisely by the supplementation with omega-3 fatty acids (omega-3 FAs) for individuals with OSA.